The Negative Association Between Positive Psychological Wellbeing and Loss Aversion - Koan, Ibuki; Nakagawa, Takumi; Chen, Chong; Matsubara, Toshio; Lei, Huijie; Hagiwara, Kosuke; Hirotsu, Masako; Yamagata, Hirotaka; Nakagawa, Shin (Frontiers in Psychology, 2021)
When making decisions, people tend to overweigh the impact of losses compared to gains, a phenomenon known as loss aversion (LA). A moderate amount of LA may be adaptive as it is necessary for protecting oneself from danger. However, excessive LA may leave people few opportunities and ultimately lead to suboptimal outcomes. Despite frequent reports of elevated LA in specific populations such as patients with depression, little is known about what psychological characteristics are associated with the tendency of LA. Based on the neurobiological studies of LA, we hypothesized that positive psychological wellbeing may be negatively associated with people’s tendency of LA. In the present study, we set out to test this hypothesis in a sample of young adults. We evaluated LA using a decision-making task in which subjects were asked to decide whether to accept or reject a series of coin-toss gambles. Our results revealed that individuals with more advanced personal growth as assessed by the Ryff's Psychological Well-being Inventory showed reduced LA. To our knowledge, this is the first report demonstrating an association between positive psychological wellbeing and LA. These findings suggest that personal growth may be employed as interventional targets for correcting excessive LA in vulnerable populations.